PENGARUH ROTASI PEKERJAAN TERHADAP KINERJA PEGAWAI PADA PT POS INDONESIA (PERSERO) KANTOR CABANG UTAMA KOTA BANDUNG - Widia Auliya; Widwi Handari Adji (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The purpose of the study is to investigate for and analyze an impact of job rotation variables on employee performance. The PT Pos Indonesia (Persero) Bandung City Main Branch Office is the focus of the investigation. In this study, a quantitative descriptive method is employed. For data collection techniques, questionnaires are distributed to a sample of 55 employees, whose responses will be processed and analyzed. Statistical tests, such as the t test, serve as the method of data analysis for testing the hypothesis. Before the data, the validity and analyzing dependability were evaluated to determine the data's quality. The findings revealed that position rotation has a positive and statistically significant impact on employee performance. This is demonstrated by the rotation of job variables, which influence employee performance variables by 70.2%, while the remaining 29.8% explains the influence of variables outside the scope of the study. With the job rotation at PT Pos Indonesia (Persero) Bandung, it is hoped that it will be implemented properly so that employees do not feel bored and monotonous about their work or position.